STUDENTS’ ANXIETY IN SPEAKING ENGLISH (A CASE STUDY IN ONE HOTEL AND TOURISM COLLEGE IN BANDUNG) - Septy Indrianty (STKIP Siliwangi, 2016)
This study investigated students’ anxiety in speaking English in one Hotel and Tourism College in Bandung. This study examined types of anxiety, and source anxiety. This study was implementing characteristic of a case study. The data were obtained through observation of class interaction and interview. The data were analyzed descriptively and interpreted to answer the research question. The study revealed two findings related to research questions. First, two types of anxiety were evidenced, i.e. trait anxiety and state/situational anxiety. Second, the students’ anxiety in English speaking class was derived from three main sources of anxiety, i.e. communication apprehension, test anxiety and fear of negative evaluation. Moreover, as the interview data revealed, lack of vocabularies and lack of preparation have also contributed to students’ anxiety in speaking. These findings suggest that the teacher should be more aware of students’ anxiety in order to arouse students’ motivation to speak up confidently and fluently in an English speaking class. As such, teachers are urged to be fairly creative in devising better technique that could encourage the students to speak more. Keywords: anxiety, speaking English, factor of anxiety